Web-Based Auction Information System at PT. Pegadaian Medan - Yusuf Ijonris; Tamado Simon Sagala (International Journal of Scientific Multidisciplinary Research, 2025)
The development of the world of technology today is very fast. Technology has been used in various aspects of people's lives, especially the internet. The application of this internet technology makes it easier for people to access information because there are no limitations in terms of access to information. On this occasion, the researcher tried to develop a WEB-Based Pawn Auction System. The online auction service provider is the committee auctioning off customer auction items that are due and the buyer makes a price offer. This Pawn Auction Service Provider Service that is due is made using the PHP programming language, MySQL database, and XAMPP 1.6 webserver. This application will be made web-based so that it is easy to access by various parties and uses a user-friendly interface so that it is comfortable to use. This application can be run on various existing internet web browsers. In creating this application, the researcher concluded that the existence of the Pawnshop Auction Service Provider will increasingly open up opportunities for the wider community to get the chance to auction and obtain auctioned goods in the form of auctioned goods that have matured at a price that is cheaper than the market price